1985
DOI: 10.1177/002795018511300107
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the PSBR

Abstract: Most economists would doubtless reject the idea that policy makers or the public should judge budgets solely in terms of a single summary concept, surplus or deficit. Yet there is an undoubted demand for a single statistic which provides at least a rough-and-ready summary of the fiscal position. The attempt to specify such a single statistic has given rise to controversy for many years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In fact, the idea of using the public sector net worth figure as a tool to enhance macro‐economic management is not a new concept. It can, for instance, be traced back to debates by UK government officials and academics in the mid‐1980s, with Odling‐Smee and Riley (1985), both from HM Treasury, arguing that it would be ideal for medium to long‐term governmental debt to be managed so that the public sector balance sheet's net worth measure remained unchanged. Britton (1987), the then director of the National Institute of Economic and Social Research (NIESR), supported Odling‐Smee and Riley when he argued that it would be financially prudent for the government to ensure that the real net worth of the public sector was not eroded, but should instead be made to grow roughly in line with real incomes, unless there were extenuating circumstances to warrant departure from such a policy (e.g., in times of war or in a major emergency).…”
Section: The Attraction Of Wga To Governmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the idea of using the public sector net worth figure as a tool to enhance macro‐economic management is not a new concept. It can, for instance, be traced back to debates by UK government officials and academics in the mid‐1980s, with Odling‐Smee and Riley (1985), both from HM Treasury, arguing that it would be ideal for medium to long‐term governmental debt to be managed so that the public sector balance sheet's net worth measure remained unchanged. Britton (1987), the then director of the National Institute of Economic and Social Research (NIESR), supported Odling‐Smee and Riley when he argued that it would be financially prudent for the government to ensure that the real net worth of the public sector was not eroded, but should instead be made to grow roughly in line with real incomes, unless there were extenuating circumstances to warrant departure from such a policy (e.g., in times of war or in a major emergency).…”
Section: The Attraction Of Wga To Governmentmentioning
confidence: 99%
“…Other advocates, such as Buiter (1985), an economist and former member of the Bank of England's Monetary Policy Committee, also suggested that the adoption of a balance sheet approach could help to improve the quality of information used in the management of public sector finances. Buiter (1985), however, went further than the proposals put forward by Odling‐Smee and Riley (1985), arguing for a more ‘comprehensive’ public sector balance sheet model. His proposed model was very future oriented and sought to take account (using actuarial‐based measures) of the present value of future income streams (relying on the government's sovereign right to set taxes in order to justify the reasonableness of such an action), and the present value of future spending commitments (see reviews of the model in HM Treasury, 2002; and Britton, 1987).…”
Section: The Attraction Of Wga To Governmentmentioning
confidence: 99%
See 3 more Smart Citations